Autophagy Regulates Fungal Virulence and Sexual Reproduction in Cryptococcus neoformans - Jiang, Su-Ting; Chang, An-Ni; Han, Lian-Tao; Guo, Jie-Shu; Li, Yuan-Hong; Liu, Tong-Bao (Frontiers in Cell and Developmental Biology, 2020)
Autophagy (macroautophagy) is an evolutionarily conserved degradation pathway involved in bulk degradation of cytoplasmic organelles, old protein, and other macromolecules and nutrient recycling during starvation. Extensive studies on functions of autophagy-related genes have revealed that autophagy plays a role in cell differentiation and pathogenesis of pathogenic fungi. In this study, we identified and characterized 14 core autophagy machinery genes (ATGs) in C. neoformans. To understand the function of autophagy in virulence and fungal development in C. neoformans, we knocked out the 14 ATGs in both ⍺ and a mating type strain backgrounds in C. neoformans, respectively, by using biolistic transformation and in vivo homologous recombination. Fungal virulence assay showed that virulence of each atgΔ mutants was attenuated in a murine inhalation systemic-infection model, although virulence factor production was not dramatically impaired in vitro. Fungal mating assays showed that all the 14 ATGs are essential for fungal sexual reproduction as basidiospore production was blocked in bilateral mating between each atgΔ mutants. Fungal nuclei development assay showed that nuclei in the bilateral mating of each atgΔ mutants failed to undergo meiosis after fusion, indicating autophagy is essential for regulating meiosis during mating. Overall, our study showed that autophagy is essential for fungal virulence and sexual reproduction in C. neoformans, which likely represents a conserved novel virulence and sexual reproduction control mechanism that involves the autophagy-mediated proteolysis pathway.